Mathematical Modelling Of The Passive And Semi-Active Automobile Suspension Systems In Ford Scorpio Car Model - Yahaya, Saifudin Hafiz; Yaakub, Siti Farizah; Salleh, Mohd Shukor; Abd Rashid, Mohd Warikh; Abdullah, Abu; Purnomo, Muhammad Ridwan Andi (Penerbit Universiti Teknikal Malaysia Melaka, 2019)
The suspension is a system of spring or shock absorbers connecting the wheels and axles at the chassis of a vehicle. In this study, Ford Scorpio car with passive and semi-active suspension system are formulated using Second Order Differential Equations (ODE). These models were solved analytically using the undetermined coefficient and Cramer rule methods. The comparison between passive and semi-active suspension system also conducted to measure such as displacement, frequency and time by plotting graphs. The passive system resulted that a constant displacement roughly at 0.035 m while 0.025 m was obtained by a semi-active suspension system. Semiactive system took t = 1 s to yield a constant displacement while for the passive suspension system required t = 1.5 s. The comparison showed the semi-active results were better than a passive suspension system.